2016
DOI: 10.1007/s11095-016-1890-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Solid Dispersion of Itraconazole Prepared by Solubilization in Concentrated Aqueous Solutions of Weak Organic Acids and Drying

Abstract: A method of highly solubilizing an extremely water-insoluble drug, ITZ, in aqueous media and converting it into an amorphous form in a physically stable SD was successfully investigated. The dissolution rate and the extent of supersaturation of the drug in dissolution media improved greatly, and any precipitate formed at high pH had very small particle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…As the drug was completely solubilized in the lipid matrix, the crystallinity of the drug was lost and an homogenous formulation was achived with the amorphous nature of ITZ in the formulation. This observation is in accordance with reported studies ( Lim et al, 2014 ; Parikh et al, 2016 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…As the drug was completely solubilized in the lipid matrix, the crystallinity of the drug was lost and an homogenous formulation was achived with the amorphous nature of ITZ in the formulation. This observation is in accordance with reported studies ( Lim et al, 2014 ; Parikh et al, 2016 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…In a recent report, Parikh et al (51) reported that ITZ forms hydrogen bonds with the -OH groups present in succinic and other weak acids. In a recent report, Parikh et al (51) reported that ITZ forms hydrogen bonds with the -OH groups present in succinic and other weak acids.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Sometimes, in order to enhance stability, instead of using citric acid alone as a co-former, citric acid can be used as a part of the co-former as was the case for citric acid–L-arginine, which was used as a co-former for carbamazepine [ 120 ]. Citric acid can interact with basic drugs and form hydrogen bonds leading to drug amorphization and increased solubility [ 121 ]. The solubility of difficult to solubilize basic drugs such as haloperidol and itraconazole was increased when these drugs interacted with citric acid and formed stable amorphous solid dispersions [ 122 , 123 ].…”
Section: Citric Acid In Formulationsmentioning
confidence: 99%